Multiple Metastases of the Liver and Lung After Breast-Conserving Surgery for Ductal Carcinoma In Situ Without Microinvasion of the Breast: A Case Report and Literature Review - Wang, Zhen; Zhang, Xinyang; Ren, Huiyang; Zhang, Lei; Chen, Bo (Frontiers in Oncology, 2022)
Background: Ductal carcinoma in situ (DCIS) is a non-invasive disease that rarely causes distant metastasis. It is extremely rare for patients diagnosed with DCIS without microinvasion to develop distant metastasis in the absence of ipsilateral or contralateral breast recurrence. This is the first case report of multiple liver and lung metastases from DCIS after breast-conserving surgery and radiotherapy. Case presentation: A 45-year-old woman who was diagnosed with DCIS received breast-conserving surgery, radiotherapy, and sequential endocrine therapy developed multiple metastases in the liver and lung despite not having bilateral breast recurrence at the 62-month follow-up. Comprehensive advanced breast cancer therapy was administered, but did not prevent progression of metastatic foci in the liver. Conclusions: This case shows the poor potential outcome in DCIS. Further research should be conducted on metastasis in DCIS; reexamination and monitoring are indispensable for patients diagnosed with DCIS.